Polyunsaturated Fatty Acids and Human Health: A Key to Modern Nutritional Balance in Association with Polyphenolic Compounds from Food Sources - Magdalena Mititelu; Dumitru Lupuliasa; Sorinel Marius Neacșu; Gabriel Olteanu; Ștefan Sebastian Busnatu; Andreea Mihai; Violeta Popovici; Nicoleta Măru; Steluța Constanța Boroghină; Sebastian Mihai; Corina-Bianca Ioniță-Mîndrican; Alexandru Scafa-Udriște (Foods)
Polyunsaturated fatty acids (PUFAs) are vital dietary elements that play a significant role in human nutrition. They are highly regarded for their positive contributions to overall health and well-being. Beyond the fact that they provide a substantial supply of energy to the body (a role that saturated fats can also perform), these unsaturated fatty acids and, especially, the essential ones are involved in cell membrane structure, blood pressure regulation, and coagulation; participate in the proper functioning of the immune system and assimilation of fat-soluble vitamins; influence the synthesis of pro- and anti-inflammatory substances; and protect the cardiovascular system. Modern diets like the Western diet and the American diet are rich in saturated fats found especially in fast food products, sweets, and processed foods, a fact that has led to an increase in the prevalence of metabolic diseases worldwide (obesity, type II diabetes, gout, cardiovascular disease). Nutritionists have drawn attention to the moderate consumption of saturated fats and the need to increase the intake of unsaturated fats to the detriment of saturated ones. This paper examines the biochemical roles of polyunsaturated fats, particularly essential fatty acids, and contrasts their benefits with the detrimental effects of saturated fat overconsumption. Furthermore, it highlights the necessity for dietary shifts towards increased PUFA intake to mitigate the global burden of diet-related health issues. The co-occurrence of PUFAs and polyphenols in plant-based foods highlights the sophistication of nature’s design. These bioactive compounds are not randomly distributed but are present in foods humans have consumed together historically. From traditional diets like the Mediterranean, which pairs olive oil (PUFAs and polyphenols) with vegetables and legumes, to Asian cuisines combining sesame seeds with turmeric, cultural practices have long harnessed this natural synergy.